Composite metal catalyst as well as preparation method and application thereof in co-production of diethylenetriamine and piperazine

By using composite metal catalysts composed of metals such as Ni, Cu, etc., the problems of low catalyst activity, poor selectivity, short life and high cost in industrial production of diethylene triamine are solved, and efficient diethylene triamine and piperazine are achieved. The stability and economicality of the catalyst are improved.

CN119386882APending Publication Date: 2025-02-07SHAOXING XINGXIN CHEM

Patent Information

Application Number
CN202411513769.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, the industrial production of diethylene triamine faces the problems of low catalyst activity, poor selectivity, short life and high cost, resulting in low raw material conversion rate and poor product selectivity.

Method used

The composite metal catalyst consisting of the main active component (Ni, Cu), the co-active component (Mg, Cr, Mn, Co, Sr, La, Ba) and the support Al2O3 was prepared by co-precipitation-kneading and extrusion method. Reduction activation is carried out in a fixed bed reactor to improve the activity and stability of the catalyst.

Benefits of technology

The monoethanolamine conversion rate was achieved above 93.45%, the overall selectivity of diethylene triamine and piperazine was between 85.82% and 98.00%, the diethylene triamine selectivity was between 66.79% and 81.33%, and the piperazine selectivity was between 8.11% and 29.22 %, and the stability test of the catalyst showed that the conversion rate of monoethanolamine was maintained above 88.05%, and the selectivity of diethylene triamine was maintained above 79.32%, which solved the problems of low raw material conversion rate and poor product selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005106131590000051
    Figure BDA0005106131590000051
  • Figure BDA0005106131590000141
    Figure BDA0005106131590000141
  • Figure BDA0005106131590000151
    Figure BDA0005106131590000151
Patent Text Reader

Abstract

The invention belongs to the field of catalyst preparation and compound synthesis, and particularly relates to a composite metal catalyst, a preparation method and application of the composite metal catalyst in co-production of diethylenetriamine and piperazine. The composite metal catalyst consists of three parts, namely a main active component, an auxiliary active component and a carrier, the main active component is at least any one of Ni and Cu, the auxiliary active component is at least any one of Mg, Cr, Mn, Co, Sr, La and Ba, and the carrier is Al2O3. The invention also provides a method for co-production of piperazine from diethylenetriamine by using the composite metal catalyst. By adopting the method disclosed by the invention, the coproduction of the piperazine with high added value in the continuous synthesis process of the diethylenetriamine can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalyst preparation and compound synthesis, and specifically relates to a composite metal catalyst and a preparation method thereof, and application thereof in the co-production of piperazine with diethylenetriamine. Background Art

[0002] Diethylenetriamine (DETA) and piperazine (PIP) are two important fine chemical intermediates, which are widely used in many fields, such as resin curing agents, demulsifiers, surfactants, metal chelating agents, lubricant additives, pharmaceutical intermediates, pesticides, dyes and preservatives;

[0003] At present, the industrial methods for synthesizing diethylenetriamine include the dichloroethane amination method, the ethylenediamine (EDA) hydrogenation method and the monoethanolamine (MEA) method. The details are as follows:

[0004] 1. Ethylene dichloride amination method:

[0005] Due to the serious corrosion to equipment, high energy consumption and high production cost of the ethylene dichloride amination method, it has been gradually replaced by other methods.

[0006] 2. Ethylenediamine hydrogenation method:

[0007] CN 108772074B discloses a catalyst for preparing diethylenetriamine by hydrogenation of ethylenediamine and a preparation method thereof. The catalyst selects rare earth metals and precious metal palladium to modify non-precious metals such as copper, cobalt, nickel and cobalt. -1 The results show that the conversion rate of ethylenediamine is less than 40%. This process has high requirements on catalyst activity, often requires the addition of precious metals, and has low raw material conversion rate and poor selectivity.

[0008] 3. Monoethanolamine method:

[0009] Although the monoethanolamine method has the advantages of low energy consumption and good atom economy, the reaction conditions are harsh (reaction pressure 20.0-30.0 MPa), and the product is mainly ethylenediamine, with low selectivity for diethylenetriamine and piperazine.

[0010] Based on this, researchers proposed a synthetic route using monoethanolamine and ethylenediamine as raw materials. CN114605268B provides a method for catalytic synthesis of polyethylene polyamines, which discloses that monoethanolamine, ethylenediamine and ammonia are used as raw materials, and metals such as Ni, Co, Cu, Ru, Ir, Mn, B, and W are impregnated on a carrier modified with Na and K by an impregnation method, and are used for catalytic synthesis of polyethylene polyamines under the conditions of a temperature of 150 to 200°C, a H2 pressure of 6 to 26 MPa, and a molar ratio of monoethanolamine to ethylenediamine of 0 to 5:1. The conversion rate of monoethanolamine is 43.8% to 85.9%, the selectivity of diethylenetriamine is 50.5% to 71.2%, and the selectivity of piperazine is 3.1% to 8.7%. Although the method has a high selectivity for diethylenetriamine, the catalyst formula (catalyst 8) with the best effect contains Re precious metal, the price cost is high, and the preparation process is complicated. At the same time, the impregnation method is difficult to ensure a longer catalyst service life during industrial application.

[0011] In summary, the industrial production of diethylenetriamine depends on the activity of the catalyst. The realization of industrial production of diethylenetriamine requires the catalyst to have advantages such as high activity, good selectivity, long life and low price. Therefore, how to effectively solve the above problems has become a key link in the industrialization of diethylenetriamine. Summary of the invention

[0012] The technical problem to be solved by the present invention is to provide a composite metal catalyst and a preparation method thereof and application thereof in the co-production of piperazine from diethylenetriamine.

[0013] In order to solve the above technical problems, the present invention provides a composite metal catalyst, which consists of three parts: a main active component, an auxiliary active component and a carrier;

[0014] The main active component is at least any one of Ni and Cu (i.e., one or a combination of two), the auxiliary active component is at least any one of Mg, Cr, Mn, Co, Sr, La, and Ba (i.e., one or a combination of two), and the carrier is Al2O3;

[0015] The main active component accounts for 20% to 40% of the total weight of the composite metal catalyst, the auxiliary active component accounts for 2% to 10% of the total weight of the composite metal catalyst, and Al2O3 accounts for 50% to 78% of the total weight of the composite metal catalyst.

[0016] The composite metal catalyst is used for catalyzing the reaction of monoethanolamine and ethylenediamine to prepare diethylenetriamine and co-produce piperazine.

[0017] As an improvement of the composite metal catalyst of the present invention: the main active component accounts for 20% to 35% of the total weight of the composite metal catalyst, the auxiliary active component accounts for 5% to 10% of the total weight of the composite metal catalyst, and Al2O3 accounts for 55% to 78% of the total weight of the composite metal catalyst.

[0018] As a further improvement of the composite metal catalyst of the present invention: the main active component accounts for 25% to 35% of the total weight of the composite metal catalyst, the auxiliary active component accounts for 5% to 7% of the total weight of the composite metal catalyst, and Al2O3 accounts for 58% to 70% of the total weight of the composite metal catalyst.

[0019] As a further improvement of the composite metal catalyst of the present invention: the main active component is composed of Ni and Cu, Ni accounts for 20% of the total weight of the composite metal catalyst, and Cu accounts for 10% of the total weight of the composite metal catalyst;

[0020] The auxiliary active components are Sr and La, wherein Sr accounts for 5% of the total weight of the composite metal catalyst and La accounts for 2% of the total weight of the composite metal catalyst;

[0021] Al2O3 accounts for 63% of the total weight of the composite metal catalyst.

[0022] The present invention also provides a method for preparing the composite metal catalyst, comprising the following steps:

[0023] 1) Dissolve the metal nitrate corresponding to the main active component and the metal nitrate corresponding to the auxiliary active component in deionized water, and the resulting solution is named solution A;

[0024] In solution A, the sum of the concentrations of the metal nitrate corresponding to the main active component and the metal nitrate corresponding to the auxiliary active component is 0.5 to 2.0 mol / L (preferably 0.5 to 1.5 mol / L);

[0025] 2) Dissolve the precipitant in deionized water, and the resulting solution is named solution B; in solution B, the concentration of the precipitant is 0.5 to 2.5 mol / L (preferably 1.0 to 2.5 mol / L);

[0026] 3) At 25-60° C. and under stirring, solution A is added dropwise to a container containing 15% to 30% by weight of deionized water to form a reaction system. During the addition of solution A, solution B is added dropwise to control the pH of the reaction system to 7 to 9 (preferably 8 to 9) until the addition of solution A is completed; the addition time of solution A is 0.5 to 3 hours;

[0027] Note: The time of adding solution A is the precipitation time; the amount of solution B is determined by controlling the pH of the reaction system;

[0028] 4) The product obtained in step 3) is aged at a temperature of 30 to 50° C. for 1 to 2 h;

[0029] After aging, the mixture was filtered and the filter cake was washed with deionized water (until the pH was neutral), and then pseudo-boehmite (as a carrier) was added and mixed evenly, and dried (dried to constant weight). The obtained mixture was named as dried mixture;

[0030] Adding a binder to the dried mixture for extrusion molding, and calcining to obtain a catalyst precursor;

[0031] Note: To ensure uniform mixing with the carrier, after the filter cake is washed for the last time (i.e. after the pH is neutral), keep the deionized water used for washing and then add the pseudo-boehmite for uniform mixing;

[0032] During the firing process, the binder is volatilized;

[0033] 5) The catalyst precursor is reduced and activated by using H2 to obtain a composite metal catalyst.

[0034] Note: Reduction activation is performed before actual use, and activation can be performed in the reaction device.

[0035] As an improvement to the preparation method of the composite metal catalyst of the present invention, in the step 3):

[0036] After the addition of solution A is completed, stirring may be continued for 0.5 to 1 hour to ensure sufficient precipitation.

[0037] As a further improvement of the preparation method of the composite metal catalyst of the present invention:

[0038] In the step 3), the precipitating agent is at least one of the following: sodium carbonate, sodium hydroxide;

[0039] In the step 4):

[0040] The binder is at least one of the following: a nitric acid solution (dilute nitric acid) with a concentration of 2% to 10%, citric acid, and sesbania powder, and the weight ratio of the binder to the dried mixture is 2% to 10% (preferably 3 to 10%);

[0041] The drying temperature is 70-120°C, and the mixture is dried to constant weight;

[0042] The calcination temperature is 400-700°C, and the calcination time is 2-6 hours.

[0043] As a further improvement of the preparation method of the composite metal catalyst of the present invention, in step 5):

[0044] The reduction activation temperature is 300-600°C, the activation time is 2-8h, and the activation H2 pressure is 1-3MPa.

[0045] The present invention also provides a method for co-producing piperazine from diethylenetriamine using a composite metal catalyst, comprising the following steps:

[0046] The fixed bed reactor is filled with a composite metal catalyst (a composite metal catalyst after reduction activation);

[0047] Monoethanolamine and ethylenediamine are mixed in a molar ratio of 1:2-5 and pumped into a fixed bed reactor as a reaction raw material, and the reaction pressure is controlled to be 2-5 MPa (preferably 2-4 MPa) by introducing H2 into the fixed bed reactor, and the volume space velocity of the raw material is 0.30-0.50 h -1 Under H2 conditions, monoethanolamine and ethylenediamine react under the catalytic action of a composite metal catalyst (a composite metal catalyst after reduction activation) at a reaction temperature of 150 to 180°C; the reaction products include diethylenetriamine and piperazine.

[0048] Note: Samples can be taken to analyze the content of diethylenetriamine and piperazine in the reaction product.

[0049] Volumetric space velocity = volumetric feed amount of reaction raw materials per unit time / catalyst volume.

[0050] As an improvement of the method for co-producing piperazine with diethylenetriamine of the present invention: the molar ratio of monoethanolamine to ethylenediamine is 1:3-5, and the volume space velocity of the raw materials is 0.30-0.45h -1 ; The reaction temperature is 150-170°C, and the reaction H2 pressure is 2-4MPa.

[0051] The present invention has the following beneficial effects:

[0052] (1) From the perspective of catalyst: The catalyst provided by the present invention, prepared by the coprecipitation-kneading extrusion method, has the advantages of good metal particle dispersion, high activity, long life and low cost;

[0053] (2) From the perspective of the synthesis process: the use of the catalyst of the present invention to synthesize diethylenetriamine and co-produce piperazine can achieve a monoethanolamine conversion rate of more than 93.45%, wherein the overall selectivity of diethylenetriamine and piperazine is 85.82% to 98.00%, the selectivity of diethylenetriamine is 66.79% to 81.33%, and the selectivity of piperazine is 8.11% to 29.22%. After a 3000-hour catalyst stability test, the monoethanolamine conversion rate is maintained at more than 88.05%, and the diethylenetriamine selectivity is maintained at more than 79.32%, thereby solving the problems of low raw material conversion rate, poor product selectivity and short catalyst life in the prior art;

[0054] (3) From the perspective of economy: the catalyst preparation steps are simple and no precious metal elements are used, which greatly reduces the production cost; at the same time, the continuous process of co-producing piperazine with diethylenetriamine can effectively improve production capacity, increase product added value, and facilitate industrial promotion.

[0055] In summary, the composite metal catalyst of the present invention solves the problems of low activity, poor stability, high cost and low product selectivity of existing catalysts. The method of the present invention can realize the co-production of high value-added piperazine in the process of continuous synthesis of diethylenetriamine. DETAILED DESCRIPTION

[0056] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:

[0057] The specific implementation process is mainly divided into two parts: catalyst preparation and the synthesis process of diethylenetriamine and piperazine.

[0058] Example 1

[0059] Step 1: Preparation of composite metal catalyst:

[0060] The mass proportion of the main active component Ni is set to 20%, the mass proportion of the auxiliary active component Sr is set to 5%, the mass proportion of La is set to 2% (that is, the total mass proportion of the auxiliary active components is 7%), and the mass proportion of the carrier Al2O3 is set to 73%.

[0061] Follow these steps in order:

[0062] (1) Weigh 0.341 mol of nickel nitrate hexahydrate (containing 20 g of nickel), 0.057 mol of strontium nitrate (containing 5 g of strontium) and 0.014 mol of lanthanum nitrate hexahydrate (containing 2 g of lanthanum), add deionized water (fixed to 206 mL) to dissolve, thereby preparing a 2.0 mol / L metal nitrate solution; marked as solution A;

[0063] (2) Prepare an appropriate amount of anhydrous sodium carbonate with deionized water to prepare a 2.0 mol / L alkaline solution, labeled as solution B;

[0064] (3) Set the precipitation temperature to 50°C;

[0065] At 50°C, solution A was added dropwise to a beaker containing about 60 mL of deionized water under stirring to form a reaction system. During the addition of solution A, solution B was added dropwise to control the pH of the reaction system to 8-9. The stirring was maintained during the addition process until the addition of solution A was completed (the addition time of solution A was generally about 30 min), and stirring was continued for 30 min before stopping.

[0066] (4) The product obtained in step (3) was aged at 50° C. for 1 h, filtered after aging, and the filter cake was washed with deionized water until pH = 7. After the last washing, the deionized water used for washing was retained, and 97.33 g of pseudo-boehmite (containing 73 g of Al2O3) was directly added to mix evenly, and dried at 70° C. to constant weight. The obtained mixture was named as dried mixture;

[0067] Dilute nitric acid (mass concentration of 2%) and citric acid as a binder were added to the dried mixture for extrusion (diameter of about 3 mm, length of about 0.5-5 cm), and calcined at 500°C for 4 hours to obtain a catalyst precursor; and then the catalyst precursor was folded into strips with a length of 0.5 cm to 1 cm.

[0068] Dilute nitric acid accounts for 5% by mass of the dried mixture and citric acid accounts for 5% by mass of the dried mixture.

[0069] Note: During the above roasting process, the precipitate is roasted into metal oxides, etc., and the dilute nitric acid and citric acid are volatilized.

[0070] (5) The catalyst precursor obtained in step (4) was loaded into a fixed bed (catalyst loading 80 mL), and reduced and activated with 2 MPa H2 at 400°C for 4 h to obtain the activated catalyst 1---Ni 20 Sr5La2 / Al2O3.

[0071] Description: Hydrogen activation reduces metal oxides to metal elements.

[0072] Step 2: Co-production of piperazine with diethylenetriamine:

[0073] Using the activated catalyst 1 obtained above---Ni 20 Sr5La2 / Al2O3, a co-production test of diethylenetriamine (DETA) and piperazine (PIP) was carried out in a fixed bed: monoethanolamine (MEA) and ethylenediamine (EDA) were mixed in a set molar ratio and pumped into a fixed bed reactor as reaction raw materials, and the reaction pressure (reaction H2 pressure) was controlled by adding H2 to the fixed bed reactor.

[0074] The experimental conditions are as follows: the molar ratio of the reaction materials is MEA:EDA=1:3, and the volumetric space velocity is 0.30h -1 , the reaction temperature is 150°C, and the reaction H2 pressure is 3MPa.

[0075] Monoethanolamine and ethylenediamine react with H2 under the action of the activated composite metal catalyst as follows:

[0076]

[0077] The reaction product contains diethylenetriamine and piperazine.

[0078] Description: The test results were analyzed by gas chromatography to calculate the conversion of monoethanolamine (MEA), diethylenetriamine (DETA) and piperazine (PIP) selectivity. The results are shown in Table 1.

[0079] Monoethanolamine conversion rate = 1-(unconverted monoethanolamine / total amount of monoethanolamine in raw materials) × 100%;

[0080] Diethylenetriamine selectivity = (amount of diethylenetriamine produced / conversion rate of monoethanolamine) × 100%;

[0081] Piperazine selectivity = (amount of piperazine produced / conversion rate of monoethanolamine) x 100%.

[0082] Example 2

[0083] Step 1: Preparation of composite metal catalyst:

[0084] The mass proportion of the main active component Cu is set to 20%, the mass proportion of the auxiliary active component Sr is set to 5%, the mass proportion of La is set to 2% (ie, the total mass proportion of the auxiliary active components is 7%), and the mass proportion of the carrier is set to 73%.

[0085] Follow these steps in order:

[0086] (1) 0.341 mol of nickel nitrate hexahydrate was replaced with 0.313 mol of copper nitrate trihydrate (containing 20 g of copper); the rest was the same as (1) to (4) of step 1 of Example 1;

[0087] (2) The folded catalyst precursor was loaded into a fixed bed (catalyst loading 80 mL) and reduced and activated with 3 MPa H2 at 300 °C for 8 h to obtain the activated catalyst 2---Cu 20 Sr5La2 / Al2O3;

[0088] Step 2: Co-production of piperazine with diethylenetriamine:

[0089] Using the activated catalyst 2 obtained above, Cu 20 Sr5La2 / Al2O3, diethylenetriamine and piperazine co-production test was carried out in a fixed bed, the test conditions are as follows:

[0090] The molar ratio of the reaction materials is MEA:EDA=1:3, and the volumetric space velocity is 0.30h -1 , reaction temperature: 180°C, reaction H2 pressure: 3MPa. The results are shown in Table 1.

[0091] Example 3

[0092] Step 1: Preparation of composite metal catalyst:

[0093] The mass proportion of the main active component Ni is set to 20%, the mass proportion of Cu is set to 10% (that is, the total proportion of the main active components is 30%), the mass proportion of the auxiliary active component Sr is set to 5%, the mass proportion of La is set to 2% (that is, the total proportion of the auxiliary active components is 7%), and the mass proportion of the carrier Al2O3 is set to 63%.

[0094] Follow these steps in order:

[0095] (1) Weigh 0.341 mol of nickel nitrate hexahydrate (containing 20 g of nickel), 0.156 mol of copper nitrate trihydrate (containing 10 g of copper), 0.057 mol of strontium nitrate (containing 5 g of strontium) and 0.014 mol of lanthanum nitrate hexahydrate (containing 2 g of lanthanum), add deionized water to make the volume to 1136 mL to dissolve, and prepare a 0.5 mol / L metal nitrate solution, which is marked as solution A;

[0096] (2) 0.532 mol of anhydrous sodium carbonate and 0.507 mol of sodium hydroxide were added to deionized water to make the volume to 1039 mL to prepare a 1.0 mol / L alkaline solution, which was labeled as solution B.

[0097] (3) Set the precipitation temperature to 60°C;

[0098] At 60°C, solution A was added dropwise to a beaker containing about 170 mL of deionized water under stirring to form a reaction system. During the addition of solution A, solution B was added dropwise to control the pH of the reaction system to 8-9. The stirring was maintained during the addition process until the addition of solution A was completed (the addition time of solution A was generally about 165 min), and stirring was continued for 30 min before stopping.

[0099] (4) The product obtained in step (3) was aged at 40° C. for 1 h, filtered after aging, and the filter cake was washed with deionized water until pH = 7. After the last washing, the deionized water used for washing was retained, and 84 g of pseudo-boehmite (containing 63 g of Al2O3) was directly added to mix evenly, and dried at 120° C. to constant weight. The obtained mixture was named as dried mixture;

[0100] Add citric acid and sesbania powder as a binder to the dried mixture for extrusion and calcination at 700° C. for 2 hours to obtain a catalyst precursor; and then fold the catalyst precursor into strips with a length of 0.5 cm to 1 cm.

[0101] The citric acid accounted for 5% by mass of the dried mixture and the sesbania powder accounted for 3% by mass of the dried mixture.

[0102] Note: During the above roasting process, the precipitate is roasted into metal oxides, etc., and the citric acid and sesbania powder are volatilized.

[0103] (5) The catalyst precursor obtained in step (4) was loaded into a fixed bed (catalyst loading 80 mL), and reduced and activated with 1 MPa H2 at 600°C for 2 h to obtain the activated catalyst 3---Ni 20 Cu 10 Sr5La2 / Al2O3.

[0104] Step 2: Co-production of piperazine with diethylenetriamine:

[0105] Using the activated catalyst 3 obtained above, Ni 20 Cu 10 Sr5La2 / Al2O3, diethylenetriamine and piperazine co-production test was carried out in a fixed bed, the test conditions are as follows:

[0106] The molar ratio of the reaction materials is MEA:EDA=1:5, and the volumetric space velocity is 0.30h -1 , reaction temperature: 160°C, reaction H2 pressure: 4MPa. The results are shown in Table 1.

[0107] Example 4

[0108] Step 1: Preparation of composite metal catalyst:

[0109] The mass proportion of the main active component Ni is set to 20%, the mass proportion of Cu is set to 10% (that is, the total proportion of the main active components is 30%), the mass proportion of the auxiliary active component Mn is set to 5%, the mass proportion of Mg is set to 2% (that is, the total proportion of the auxiliary active components is 7%), and the carrier accounts for 63%.

[0110] Follow these steps in order:

[0111] (1) Weigh 0.341 mol of nickel nitrate hexahydrate (containing 20 g of nickel), 0.156 mol of copper nitrate trihydrate (containing 10 g of copper), 0.091 mol of manganese nitrate hexahydrate (containing 5 g of manganese) and 0.082 mol of magnesium nitrate hexahydrate (containing 2 g of magnesium), add deionized water to 670 mL to dissolve, and prepare a 1.0 mol / L metal nitrate solution in a beaker, marked as solution A;

[0112] (2) Weigh an appropriate amount of anhydrous sodium carbonate and add deionized water to prepare a 1.0 mol / L alkaline solution, labeled as solution B;

[0113] (3) Set the precipitation temperature to 25°C,

[0114] At 25°C, solution A was added dropwise to a beaker containing about 100 mL of deionized water under stirring to form a reaction system. During the addition of solution A, solution B was added dropwise to control the pH of the reaction system to 8-9. Stirring was maintained during the addition process until the addition of solution A was completed (the addition time of solution A was generally about 100 min), and stirring was continued for 30 min before stopping.

[0115] (4) The product obtained in step (3) was aged at 30° C. for 1 h, filtered after aging, and the filter cake was washed with deionized water until the pH value was 7. After the last washing, the deionized water used for washing was retained, and 84 g of pseudo-boehmite (containing 63 g of Al2O3) was directly added to the mixture, mixed evenly, and dried at 70° C. to constant weight. The mixture was named as dried mixture;

[0116] Add sesbania powder as a binder to the dried mixture for extrusion and calcination at 400° C. for 6 hours to obtain a catalyst precursor; and then fold the catalyst precursor into strips with a length of 0.5 cm to 1 cm.

[0117] The sesbania powder accounted for 3% of the mass of the oven-dried mixture.

[0118] (5) The catalyst precursor obtained in step (4) was loaded into a fixed bed (catalyst loading 80 mL), and reduced and activated with 2 MPa H2 at 400°C for 4 h to obtain the activated catalyst 4---Ni 20 Cu 10 Mn5Mg2 / Al2O3;

[0119] Step 2: Co-production of piperazine with diethylenetriamine:

[0120] Using the activated catalyst 4 obtained above, Ni 20 Cu 10 Mn5Mg2 / Al2O3, diethylenetriamine and piperazine co-production test was carried out in a fixed bed, the test conditions were as follows: the molar ratio of the reaction raw materials was MEA:EDA=1:2, the volume space velocity was 0.375h -1 , reaction temperature: 155°C, reaction H2 pressure: 4MPa. The results are shown in Table 1.

[0121] Example 5

[0122] Step 1: Preparation of composite metal catalyst:

[0123] The mass proportion of the main active component Ni is set to 20%, the mass proportion of Cu is set to 5% (that is, the total proportion of the main active components is 25%), the mass proportion of the auxiliary active components Co is set to 5%, the mass proportion of Ba is set to 3%, the mass proportion of Mg is set to 2% (that is, the total proportion of the auxiliary active components is 10%), and the mass proportion of the carrier Al2O3 is set to 65%.

[0124] In the preparation steps:

[0125] According to the above ratio, corresponding amounts of nickel nitrate hexahydrate, copper nitrate trihydrate, cobalt nitrate hexahydrate, barium nitrate, and magnesium nitrate hexahydrate are weighed and dissolved in deionized water to prepare a 2.0 mol / L metal nitrate solution, which is marked as solution A;

[0126] Prepare 2.5 mol / L alkaline solution (sodium carbonate solution), recorded as solution B;

[0127] The precipitation temperature is 40°C, the amount of deionized water in the beaker is about 15% of solution A, and the addition time of solution A is about 45 minutes;

[0128] After aging at 40°C for 1 hour, add pseudo-boehmite satisfying the above ratio;

[0129] The binder is composed of 5% citric acid and 3% sesbania powder by weight of the dried mixture;

[0130] Calcination at 500°C for 4h;

[0131] Reduction activation with 2MPa H2 at 400℃ for 4h;

[0132] The rest is with reference to step 1 of Example 1;

[0133] The activated catalyst 5---Ni 20 Cu5Co5Ba3Mg2 / Al2O3.

[0134] Step 2: Co-production of piperazine with diethylenetriamine:

[0135] Using the above activated catalyst 5---Ni 20 Cu5Co5Ba3Mg2 / Al2O3 was used to conduct a co-production test of diethylenetriamine and piperazine in a fixed bed. The test conditions were as follows: the molar ratio of the reaction materials was MEA:EDA = 1:5, and the volume space velocity was 0.375h -1 , reaction temperature: 175°C, reaction H2 pressure: 4MPa. The results are shown in Table 1.

[0136] Example 6

[0137] Step 1: Preparation of composite metal catalyst:

[0138] The mass proportion of the main active component Ni is set to 15%, the mass proportion of Cu is set to 5% (that is, the total mass proportion of the main active component is 20%), the mass proportion of the auxiliary active component Mg is set to 2%, and the mass proportion of the carrier Al2O3 is set to 78%.

[0139] In the preparation steps:

[0140] According to the above ratio, corresponding amounts of nickel nitrate hexahydrate, copper nitrate trihydrate, and magnesium nitrate hexahydrate are weighed, and deionized water is added to dissolve them, thereby preparing a 2.0 mol / L metal nitrate solution, which is marked as solution A;

[0141] Prepare 2.0 mol / L alkaline solution (sodium carbonate solution), recorded as solution B;

[0142] The precipitation temperature was set to 40°C; the amount of deionized water in the beaker was about 15% of solution A, and the addition time of solution A was about 30 min;

[0143] After aging at 40°C for 1 hour, add pseudo-boehmite satisfying the above ratio;

[0144] The binder is composed of 5% of citric acid and 3% of sesbania powder based on the mass of the dried mixture;

[0145] Calcination at 500°C for 4h;

[0146] Reduction activation with 2MPa H2 at 400℃ for 4h;

[0147] The rest is with reference to step 1 of Example 1;

[0148] The activated catalyst 6---Ni 15 Cu5Mg2 / Al2O3.

[0149] Step 2: Co-production of piperazine with diethylenetriamine:

[0150] Using the activated catalyst 6 obtained above, Ni 15 Cu5Mg2 / Al2O3 was used to conduct a co-production test of diethylenetriamine and piperazine in a fixed bed. The test conditions were as follows: the molar ratio of the reaction raw materials was MEA:EDA=1:2, and the volumetric space velocity was 0.45h -1 , reaction temperature: 175°C, reaction H2 pressure: 2MPa. The results are shown in Table 1.

[0151] Example 7

[0152] Step 1: Preparation of composite metal catalyst:

[0153] The mass proportion of the main active component Ni is set to 20%, the mass proportion of Cu is set to 5% (that is, the total proportion of the main active components is 25%), the mass proportion of the auxiliary active component Mg is set to 5%, the mass proportion of La is set to 2% (that is, the total proportion of the auxiliary active components is 7%), and the mass proportion of the carrier Al2O3 is set to 68%.

[0154] In the preparation steps:

[0155] According to the above ratio, weigh the corresponding amount of nickel nitrate hexahydrate, copper nitrate trihydrate, magnesium nitrate hexahydrate, and lanthanum nitrate hexahydrate, add deionized water to dissolve, and prepare 2.0 mol / L metal nitrate, marked as solution A;

[0156] Prepare 2.0 mol / L alkaline solution (sodium carbonate solution), recorded as solution B;

[0157] The precipitation temperature was set to 40°C, the amount of deionized water in the beaker was about 15% of solution A, and the addition time of solution A was about 40 min;

[0158] After aging at 40°C for 1 hour, add pseudo-boehmite satisfying the above ratio;

[0159] The binder is composed of 5% of citric acid and 3% of sesbania powder.

[0160] Calcination at 500°C for 4h;

[0161] Reduction activation with 2MPa H2 at 400℃ for 4h,

[0162] The rest is with reference to step 1 of Example 1;

[0163] Catalyst 7---Ni 20 Cu5Mg5La2 / Al2O3.

[0164] Step 2: Co-production of piperazine with diethylenetriamine:

[0165] Using the activated catalyst 7 obtained above, Ni 20 Cu5Mg5La2 / Al2O3 was used to conduct a co-production test of diethylenetriamine and piperazine in a fixed bed, and the test conditions were the same as those in Example 6. The results are shown in Table 1.

[0166] Example 8

[0167] Step 1: a composite metal catalyst:

[0168] The mass proportion of the main active component Ni is set to 20%, the mass proportion of Cu is set to 5% (that is, the total proportion of the main active components is 25%), the mass proportion of the auxiliary active component Cr is set to 5%, the mass proportion of La is set to 2% (that is, the total proportion of the auxiliary active components is 7%), and the mass proportion of the carrier Al2O3 is set to 68%.

[0169] The preparation method thereof is the same as step 1 of embodiment 7, except that the corresponding amount of magnesium nitrate hexahydrate is replaced by the corresponding amount of chromium nitrate nonahydrate; the rest is the same as step 1 of embodiment 7.

[0170] The activated catalyst 8---Ni 20Cu5Cr5La2 / Al2O3;

[0171] Step 2: Co-production of piperazine with diethylenetriamine:

[0172] Using the activated catalyst 8 obtained above, Ni 20 Cu5Cr5La2 / Al2O3, diethylenetriamine and piperazine co-production test was carried out in a fixed bed, and the test conditions were consistent with Example 6. The results are shown in Table 1.

[0173] Example 9

[0174] Step 1: Preparation of composite metal catalyst:

[0175] The mass proportion of the main active component Ni is set to 20%, the mass proportion of Cu is set to 20% (that is, the total proportion of the main active components is 40%), the mass proportion of the auxiliary active component Sr is set to 5%, the mass proportion of La is set to 2% (that is, the total proportion of the auxiliary active components is 7%), and the mass proportion of the carrier Al2O3 is set to 53%.

[0176] In the preparation steps:

[0177] According to the above ratio, weigh the corresponding amount of nickel nitrate hexahydrate, copper nitrate trihydrate, strontium nitrate, and lanthanum nitrate hexahydrate, add deionized water to prepare a 2.0 mol / L metal nitrate solution, marked as solution A;

[0178] Prepare 2.0 mol / L alkaline solution (sodium carbonate solution), recorded as solution B;

[0179] The precipitation temperature was set to 40°C, the amount of deionized water in the beaker was about 15% of solution A, and the addition time of solution A was about 50 min;

[0180] After aging at 40°C for 1 hour, add pseudo-boehmite satisfying the above ratio;

[0181] The binder is composed of 5% citric acid and 3% sesbania powder based on the mass of the dried mixture;

[0182] Calcination at 400°C for 4h;

[0183] Reduction activation with 2MPa H2 at 400℃ for 4h;

[0184] The rest is with reference to step 1 of Example 1;

[0185] The activated catalyst 9---Ni 20 Cu 20 Sr5La2 / Al2O3.

[0186] Step 2: Co-production of piperazine with diethylenetriamine:

[0187] Using the activated catalyst 9 obtained above, Ni 20 Cu 20 Sr5La2 / Al2O3, diethylenetriamine (DETA) and piperazine (PIP) co-production test was carried out in a fixed bed. The test conditions were as follows: the molar ratio of the reaction raw materials was MEA:EDA = 1:5, the volume space velocity was 0.50h -1 , reaction temperature is 165°C, reaction H2 pressure: 2MPa.

[0188] The results are shown in Table 1.

[0189] Example 10

[0190] Step 1: Preparation of composite metal catalyst:

[0191] The mass proportion of the main active component Ni is set to 20%, the mass proportion of Cu is set to 20% (that is, the total proportion of the main active components is 40%), the mass proportion of the auxiliary active component Sr is set to 8%, the mass proportion of La is set to 2% (that is, the total proportion of the auxiliary active components is 10%), and the mass proportion of the carrier Al2O3 is set to 50%.

[0192] In the preparation steps:

[0193] According to the above ratio, weigh the corresponding amount of nickel nitrate hexahydrate, copper nitrate trihydrate, strontium nitrate, and lanthanum nitrate hexahydrate, add deionized water to prepare a 2.0 mol / L metal nitrate solution, marked as solution A;

[0194] Prepare 2.0 mol / L alkaline solution (sodium carbonate solution), recorded as solution B;

[0195] The precipitation temperature was set to 40°C, the amount of deionized water in the beaker was about 15% of solution A, and the addition time of solution A was about 60 min;

[0196] After aging at 40°C for 1 hour, add pseudo-boehmite satisfying the above ratio;

[0197] The binder is composed of 5% of citric acid and 3% of sesbania powder.

[0198] Calcination at 400°C for 4h;

[0199] Reduction activation with 2MPa H2 at 400℃ for 4h;

[0200] The rest is with reference to step 1 of Example 1;

[0201] The activated catalyst 10---Ni 20 Cu 20 Sr8La2 / Al2O3.

[0202] Step 2: Co-production of piperazine with diethylenetriamine:

[0203] Using the activated catalyst 10 obtained above---Ni 20 Cu 20 Sr8La2 / Al2O3, diethylenetriamine (DETA) and piperazine (PIP) co-production test was carried out in a fixed bed, and the test conditions were the same as in Example 9. The results are shown in Table 1.

[0204] Embodiment 11

[0205] Step 1: Preparation of composite metal catalyst:

[0206] The mass proportion of the main active component Ni is set to 20% and the mass proportion of Cu is set to 10% (that is, the total mass proportion of the main active component is 30%), the mass proportion of the auxiliary active component La is set to 2%, and the mass proportion of the carrier Al2O3 is set to 68%.

[0207] In the preparation steps:

[0208] According to the above ratio, weigh the corresponding amount of nickel nitrate hexahydrate, copper nitrate trihydrate, and lanthanum nitrate hexahydrate, add deionized water to prepare a 2.0 mol / L metal nitrate solution, marked as solution A;

[0209] Prepare 2.0 mol / L alkaline solution (sodium carbonate solution), recorded as solution B;

[0210] Set the precipitation temperature to 40°C, the amount of deionized water in the beaker is about 15% of solution A, and the addition time of solution A is generally about 50 minutes.

[0211] After aging at 40°C for 1 hour, add pseudo-boehmite satisfying the above ratio;

[0212] The binder is composed of 5% citric acid and 3% sesbania powder based on the mass of the dried mixture;

[0213] Calcination at 400°C for 4h;

[0214] Reduction activation with 2MPa H2 at 400℃ for 4h,

[0215] The rest is with reference to step 1 of Example 1;

[0216] The activated catalyst 11---Ni 20 Cu 10 La2 / Al2O3.

[0217] Step 2: Co-production of piperazine with diethylenetriamine:

[0218] Using the above activated catalyst 11---Ni 20Cu 10 La2 / Al2O3, diethylenetriamine and piperazine co-production test was carried out in a fixed bed, the test conditions were as follows: the molar ratio of the reaction raw materials was MEA:EDA=1:3, the volume space velocity was 0.30h -1 , reaction temperature: 165°C, reaction H2 pressure: 2MPa. The results are shown in Table 1.

[0219] Example 12

[0220] The activated catalysts 1, 2, 4 to 11 were subjected to a diethylenetriamine and piperazine co-production test under the same conditions as step 2 of implementation 3. The results are shown in Table 1.

[0221] Comparative Example 1

[0222] The mass proportion of the main active component Ni is set to 10% and the mass proportion of Cu is set to 5% (i.e., the total proportion of the main active components is 15%), the mass proportion of the auxiliary active components Sr is set to 5% and the mass proportion of La is set to 2% (i.e., the total proportion of the auxiliary active components is 7%), and the mass proportion of the carrier Al2O3 is set to 78%.

[0223] The remaining steps refer to step 1 of Example 3 to obtain the activated catalyst 1′---Ni 10 Cu5Sr5La2 / Al2O3.

[0224] Using the above activated catalyst 1′---Ni 10 Cu5Sr5La2 / Al2O3, a co-production test of diethylenetriamine and piperazine was carried out in a fixed bed. The experimental conditions were the same as in Example 3. The results are shown in Table 1.

[0225] Comparative Example 2

[0226] Select the activated catalyst 1′ obtained in Comparative Example 1---Ni 10 Cu5Sr5La2 / Al2O3 was used for the co-production test of diethylenetriamine and piperazine. The test conditions were as follows: the molar ratio of the reaction materials was MEA:EDA = 1:5, and the volumetric space velocity was 0.30h -1 , reaction temperature: 140°C, reaction H2 pressure: 1MPa. The results are shown in Table 1.

[0227] Comparative Example 3

[0228] The mass proportion of Ni, the main active component, is set to be 20% and the mass proportion of Cu is set to be 10% (ie, the total mass proportion of the main active components is 30%), and the mass proportion of the carrier Al2O3 is set to be 70%.

[0229] The remaining steps refer to step 1 of Example 3 to obtain the activated catalyst 2′---Ni 20 Cu 10 / Al2O3;

[0230] Using the above activated catalyst 2′---Ni 20 Cu 10 / Al2O3, a co-production test of diethylenetriamine and piperazine was carried out in a fixed bed. The experimental conditions were the same as in Example 3. The results are shown in Table 1.

[0231] Comparative Example 4-1

[0232] The mass proportion of the main active component Co is set to 20% and the mass proportion of Cu is set to 10% (i.e., the total proportion of the main active components is 30%), the mass proportion of the auxiliary active components Sr is set to 5% and the mass proportion of La is set to 2% (i.e., the total proportion of the auxiliary active components is 7%), and the mass proportion of the carrier Al2O3 is set to 63%.

[0233] The remaining steps refer to step 1 of Example 3 to obtain the activated catalyst 3′---Co 20 Cu 10 Sr5La2 / Al2O3;

[0234] Using the above activated catalyst 3′---Co 20 Cu 10 Sr5La2 / Al2O3, a test on the co-production of diethylenetriamine and piperazine was carried out in a fixed bed. The experimental conditions were the same as in Example 3. The results are shown in Table 1.

[0235] Comparative Example 4-2

[0236] The mass proportion of the main active component Co is set to 20% and the mass proportion of Ni is set to 10% (i.e., the total proportion of the main active components is 30%), the mass proportion of the auxiliary active components Sr is set to 5% and the mass proportion of La is set to 2% (i.e., the total proportion of the auxiliary active components is 7%), and the mass proportion of the carrier Al2O3 is set to 63%.

[0237] The remaining steps refer to step 1 of Example 3 to obtain the activated catalyst 4′---Co 20 Ni 10 Sr5La2 / Al2O3;

[0238] Using the above activated catalyst 4′---Co 20 Ni 10 Sr5La2 / Al2O3, a test on the co-production of diethylenetriamine and piperazine was carried out in a fixed bed. The experimental conditions were the same as in Example 3. The results are shown in Table 1.

[0239] Comparative Example 5

[0240] The mass proportion of the main active component Co is set to 20% and the mass proportion of Cu is set to 30% (i.e., the total proportion of the main active components is 50%), the mass proportion of the auxiliary active components Sr is set to 5% and the mass proportion of La is set to 2% (i.e., the total proportion of the auxiliary active components is 7%), and the mass proportion of the carrier Al2O3 is set to 43%.

[0241] The remaining steps refer to step 1 of Example 3 to obtain the activated catalyst 5′---Co 20 Cu 30 Sr5La2 / Al2O3;

[0242] Using the above activated catalyst 5′---Co 20 Cu 30 Sr5La2 / Al2O3, a test on the co-production of diethylenetriamine and piperazine was carried out in a fixed bed. The experimental conditions were the same as in Example 3. The results are shown in Table 1.

[0243] Comparative Example 6

[0244] The mass proportion of Ni, the main active component, is set to 20% and the mass proportion of Cu is set to 30% (ie, the total mass proportion of the main active components is 50%), and the mass proportion of the carrier Al2O3 is 50%.

[0245] The remaining steps refer to step 1 of Example 3 to obtain the activated catalyst 6′---Ni 20 Cu 30 / Al2O3;

[0246] Using the above activated catalyst 6′---Ni 20 Cu 30 / Al2O3, a co-production test of diethylenetriamine and piperazine was carried out in a fixed bed. The experimental conditions were the same as in Example 3. The results are shown in Table 1.

[0247] Table 1 Performance evaluation results of different catalysts

[0248]

[0249]

[0250] Table 1 shows the results of the experiment at 50 hours.

[0251] Experiment 1: Stability experiment:

[0252] Compared with step 2 of the above embodiment 3, under the above conditions, monoethanolamine and ethylenediamine were continuously added into the fixed bed for reaction to examine the stability of the catalyst.

[0253] After 3000 hours of catalyst stability test, the results obtained were: the monoethanolamine conversion rate was maintained above 88.05%, and the diethylenetriamine selectivity was maintained above 79.32%.

[0254] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.

Claims

1. A composite metal catalyst, characterized in that It consists of three parts: main active component, auxiliary active component and carrier; The main active component is at least any one of Ni and Cu, the auxiliary active component is at least any one of Mg, Cr, Mn, Co, Sr, La, and Ba, and the carrier is Al2O3; The main active component accounts for 20% to 40% of the total weight of the composite metal catalyst, the auxiliary active component accounts for 2% to 10% of the total weight of the composite metal catalyst, and Al2O3 accounts for 50% to 78% of the total weight of the composite metal catalyst.

2. The composite metal catalyst according to claim 1, characterized in that: The main active component accounts for 20% to 35% of the total weight of the composite metal catalyst, the auxiliary active component accounts for 5% to 10% of the total weight of the composite metal catalyst, and Al2O3 accounts for 55% to 78% of the total weight of the composite metal catalyst.

3. The composite metal catalyst according to claim 2, characterized in that: The main active component accounts for 25% to 35% of the total weight of the composite metal catalyst, the auxiliary active component accounts for 5% to 7% of the total weight of the composite metal catalyst, and Al2O3 accounts for 58% to 70% of the total weight of the composite metal catalyst.

4. The composite metal catalyst according to claim 3, characterized in that: The main active components are composed of Ni and Cu, Ni accounts for 20% of the total weight of the composite metal catalyst, and Cu accounts for 10% of the total weight of the composite metal catalyst; The auxiliary active components are Sr and La, wherein Sr accounts for 5% of the total weight of the composite metal catalyst and La accounts for 2% of the total weight of the composite metal catalyst; Al2O3 accounts for 63% of the total weight of the composite metal catalyst.

5. The method for preparing a composite metal catalyst according to any one of claims 1 to 4, characterized in that The following steps are involved: 1) Dissolve the metal nitrate corresponding to the main active component and the metal nitrate corresponding to the auxiliary active component in deionized water, and the resulting solution is named solution A; In solution A, the sum of the concentrations of the metal nitrate corresponding to the main active component and the metal nitrate corresponding to the auxiliary active component is 0.5-2.0 mol / L; 2) Dissolve the precipitant in deionized water, and the resulting solution is named solution B; in solution B, the concentration of the precipitant is 0.5-2.5 mol / L; 3) At 25-60°C and under stirring, solution A is added dropwise to a container containing 15%-30% by weight of deionized water of solution A to form a reaction system. During the addition of solution A, solution B is added dropwise to control the pH of the reaction system to 7-9 until the addition of solution A is completed; the addition time of solution A is 0.5-3h; 4) The product obtained in step 3) is aged at a temperature of 30 to 50° C. for 1 to 2 h; After aging, the filter cake was filtered and washed with deionized water, and then pseudo-boehmite was added and mixed evenly, and dried. The obtained mixture was named as dried mixture; Adding a binder to the dried mixture for extrusion molding, and calcining to obtain a catalyst precursor; 5) Reduction activation of the catalyst precursor using H2; A composite metal catalyst is obtained.

6. The method for preparing the composite metal catalyst according to claim 5, characterized in that In the step 3): After the addition of solution A is completed, stirring may be continued for 0.5 to 1 hour to ensure sufficient precipitation.

7. The method for preparing a composite metal catalyst according to claim 5 or 6, characterized in that: In the step 3), the precipitating agent is at least one of the following: sodium carbonate, sodium hydroxide; In the step 4): The binder is at least one of the following: nitric acid solution with a concentration of 2% to 10%, citric acid, and sesbania powder, and the weight ratio of binder to dried mixture is 2% to 10%; The drying temperature is 70-120°C, and the mixture is dried to constant weight; The calcination temperature is 400-700°C, and the calcination time is 2-6 hours.

8. The method for preparing the composite metal catalyst according to claim 7, characterized in that In the step 5): The reduction activation temperature is 300-600°C, the activation time is 2-8h, and the activation H2 pressure is 1-3MPa.

9. A method for co-producing piperazine from diethylenetriamine using a composite metal catalyst as claimed in any one of claims 1 to 4, characterized in that The following steps are involved: A composite metal catalyst is contained in a fixed bed reactor; Monoethanolamine and ethylenediamine are mixed in a molar ratio of 1:2-5 and pumped into a fixed bed reactor as a reaction raw material, and the reaction pressure is controlled to be 2-5 MPa by introducing H2 into the fixed bed reactor, and the volume space velocity of the raw material is 0.30-0.50 h -1 Under H2 conditions, monoethanolamine and ethylenediamine react under the catalytic action of a composite metal catalyst at a reaction temperature of 150 to 180°C; the reaction products include diethylenetriamine and piperazine.

10. The method for co-producing piperazine from diethylenetriamine according to claim 9, characterized in that: The molar ratio of monoethanolamine to ethylenediamine is 1:3-5, and the volumetric space velocity of the raw material is 0.30-0.45h -1 ; The reaction temperature is 150-170°C, and the reaction H2 pressure is 2-4MPa.

Citation Information

Patent Citations

  • A catalyst for the hydrogenation of ethylenediamine to diethylenetriamine and its preparation method

    CN108772074B

  • A method for catalytic synthesis of polyethylene polyamines

    CN114605268B

Cited By

  • Synthetic method for coproduction of piperazine and N-methyl piperazine and production device used in synthetic method

    CN122516924A

  • Process for the synthesis of piperazine co-product n-methylpiperazine and the production plant used

    CN122516924B

  • Regulation and control method for coproduction of piperazine and diethylenetriamine

    CN122562763A